Habitat Characteristics Nesting Environment of Green Turtle (Chelonia mydas) Pandan Island of West Sumatera - Vani Oktavia Siahaan; Thamrin Thamrin; Afrizal Tanjung (Journal of Coastal and Ocean Sciences, 2020)
This research was conducted in February until March 2017 at Pandan Island island pandan area tourist Park Pieh Island. The purpose of this study was to investigate the characteristics of the nesting habitat of the hawksbill turtle (Chelonia mydas). The method used in this research is the survey method, with measuring directly on the habitat of hawksbill turtle covering the slope of the beach, texture of sediments, within the nest of tides, the temperature of the nest, fecundity, and the type of vegetation and predators in the nesting habitat. The results showed that the nesting habitat characteristics vary between nest with each other. Nesting beach ramps ranged 2,75-4,60º with medium sand sediment texture to coarse sand. Temperatures nest ranging between 27-31ºC. The dominant vegetation in the area is a nesting plant pandan laut (Pandanus tectorius) whereas the dominant predator was biawak (Varanus salvator).